Efek Muscle Setting Exercise Pada Kekuatan Otot Pasien Pasca Rekonstruksi Anterior Cruciate Ligament Hamstring Graft: Case - Septiono Tri Jatmiko; Wahyu Tri Sudaryanto; Iin Rohayani (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Reconstruction of Anterior Cruciate Ligament Graft Hamstring is an operation to replace the torn Anterior Cruciate Ligament (ACL) using a donor from the hamstring tendon. Physiotherapy management is useful for restore performance and ability to be able to play or return to the field after surgery, therefore in recovery we can use Muscle Setting Exercise as a type of exercise in postoperative rehabilitation. This study aims to determine the effect of muscle setting exercise in increasing muscle strength, physical and functional activity and changes in muscle size in patients after sinistra hamstring graft ACL reconstruction. After doing therapy 6 times, the result were an increase in Manual Muscle Setting which was initially worth 3+ in the left knee region to a value of 4, then changes in anthropometry which were initially 34 cm, 33,5 cm, 37,5 cm, 39 cm and 41 cm to 34 cm, 34 cm, 38 cm, 40,5 cm and 42 cm with differences in athropometry of about 5 cm in the quadripes muscle, and an increase in physical and functional activity abilities using the International Knee Documentation Committee (IKDC) index which was initially at 34,5% increased by 51,7%. Physiotherapy using muscle setting exercise can increase muscle strength and improve physical and functional activity abilities in the postoperative condition of the sinistra hamstring graft ACL reconstruction.Keywords: Anterior Cruciate Ligament Reconstruction, Hamstring Graft, Exercise Therapy, Muscle Setting Exercise, Muscle Strength